Dimensões educativas de uma experiência de pesquisa participante na Escola Municipal do Campo Nossa Senhora da Salete - Dois Vizinhos - PR - Ludwig, Tamar Cristina (2024)
This dissertation is associated with the Society, Knowledge, and Education Research Line of the Postgraduate Program in Education (PPGE) of the State University of Western Paraná (Unioeste), Francisco Beltrão campus - PR. The aim was to analyze the educational dimensions of a participant research experience at the Nossa Senhora da Salete Municipal School in Dois Vizinhos - PR. To do this, it was necessary to discuss and analyze the historical emergence of Countryside Education from the Popular Social Movements of the Countryside in Brazil, its constitution as a modality of Basic Education in the Countryside, its legislation supporting it, and its training matrices. We also discussed the relationship between Countryside Education and Agroecology, considering the productive matrices of conventional agriculture and agroecological peasant agriculture and the possible ways of working with agroecological content in public schools in the countryside. Finally, to analyze the educational dimensions of a participant research experience at the Nossa Senhora da Salete Municipal School in Dois Vizinhos - PR, a methodological sequence of participant research was implemented in its different phases. This study took a qualitative approach to participant research. At the technical level, the research focused primarily on observation, document analysis, and semi-structured interviews. The aim was to demonstrate the possibility of incorporating theoretical and practical Agroecology content into the teaching and learning process in public schools in the countryside, following the different phases of participant research, especially in the implementation of an Action Plan, after the research assembly phase, the diagnosis of the school institution, the critical analysis of the demands investigated, characterizing the educational dimensions of this whole process. The research, in this sense, became relevant in that, by capturing and analyzing the academic dimensions of a participant research experience addressing Agroecology content and practices in a public school in the countryside, it was possible to envision the construction of a school in the countryside linked to the identity of Countryside Education. The research showed that it is possible to bring the school closer to the modality of Countryside Education, through educational mediations allied to school content